Upaya Penanggulangan Peredaran Dan Penyalahgunaan Narkotika Di Lembaga Pemasyarakatan Kelas IA Tangerang - Pietro Grassio E.Y (Universitas Persada Indonesia YAI, 2022)
This research discussed about the countermeasure effort of narcotics traffic and misuse at Penitentiary Class IATangerang. Illicit traffic and misuse of narcotics has happened frequently in penitentiary of Tangerang City. Thenarcotics trafficking in penitentiary is an extraordinary crime where it is included into a transnational crime whosedoers are in an organised crime until this crime is considered as a very worrying crime for penitentiary existed in thearea of Tangerang City especially Penitentiary Class IA Tangerang. The effective countermeasure effort towards thetraffic and misuse of narcotics is highly needed in Penitentiary Class IA Tangerang. Besides, its implementation mustbe precise too. By conducting cooperation with National Board of Narcotics (BNN) Tangerang City, it is expectedthat the countermeasure effort of illicit traffic and misuse of narcotics in Penitentiary Class IA Tangerang could bedone well